CHOICE OF LANGUAGE IN THE REPORTING OF ENVIRONMENTAL NEWS IN TAIFA LEO NEWSPAPER IN KENYA - Kitonga, Nelly Nzula; Owala, Silas Odhiambo; Ombati, Jane Monyangi (International Journal of Research -GRANTHAALAYAH, 2023)
Kiswahili is recognized by the Constitution of Kenya as the national language and also the official language alongside English. It is therefore the tool of communication in both official and non official contexts.For instance, Taifa Leo newspaper presents environmental information to readers in Kiswahili. This means that many people who can read have access to news on environment. The environment is a cross-cutting and sensitive issue nationally and internationally. Environment affects the life of every creature on a daily basis in one way or another. The print media, the Taifa Leo included, which has been tasked with informing the public about the world's environmental issues, ought to do so in a way that will enable people to understand the importance of the environment and thus interact with it in a positive way. This argument stems from the belief that a person values and cares for what he or she understands. This study therefore aims to determine whether the choice of language in conveying environmental information in the Taifa Leo newspaper contributes to how the audience understands the information and ultimately the behaviours generated by that understanding. This study analysed the language features selected by journalists in reporting on environmental news in the Taifa Leo newspaper to ascertain if the choice of language contributes to the reporting of intended environmental issues and finally to explain whether the choice of language elements has any relationship with the meaning of information emerging from the environmental news.This study was conducted in a library where environmental discourse was analysed. Taifa Leo newspapers published from January 2021 to March 2022 were selected purposively, by extracting texts from the selected newspaper that had environmental information. Data was analysed based on language used in presentation of environmental information in selected texts from Taifa Leo newspapers.